Es Krim Suka Dia: A Feasibility Study on Ice Cream Supporting a Sugar-Free Diet Program - Riani , Tiara Desta; Safarohmah, Ayu Nandia; Sari, Dera Puspita; Yudha, Dinda Aini Nur Amalina; Hermawan, Hary (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2023)
‘Es Krim Suka Dia’ is an innovative ice cream product designed to support a sugar-free diet program, addressing the needs of individuals with diabetes and those on restricted diets. This product emphasises health and economic value, unlike conventional ice creams, which often use high sugar and fat content. Despite the growing popularity of various ice cream brands, there is a notable lack of health-conscious options in Java, particularly in Yogyakarta. The product targets a broad audience, including children, teenagers, and the elderly, primarily focusing on diabetes sufferers. The marketing strategy includes offering a range of flavours at affordable prices and utilizing a pre-order system through e-commerce platforms. Additionally, promotional efforts involve participating in local MSME exhibitions to increase visibility and attract potential customers. This innovation results from the